Liquidity Factors Affecting the Financial Performance of Indonesian Islamic Banking - Anwar , Deky; Muwazir, Moh. Rizal (International Journal of Psychosocial Rehabilitation, 2020)
Liquidity is a very important thing for banks to be managed properly because it will affect the continuity and sustainability of the banking business. In the case of Indonesia, the problem of banking liquidity is still a serious concern for the government, because it is based on banking failure data in Indonesia in maintaining banking liquidity conditions in 1997 which ultimately led to an economic crisis. This study aims to identify liquidity factors that contribute significantly to the performance of Islamic banking in Indonesia. The variables used in this study are CAR, CR, LR and FDR as a proxy of liquidity and ROA and ROE as a proxy of the financial performance of Islamic banking in Indonesia. The data used in this study are secondary data from reports on Islamic banking publications in Indonesia for the period of January 2008 to December 2016 which are monthly. Data is processed and analyzed with Augmented Dickey Fuller (ADF) Stationery Test as a method used to test stationary data and then test hypotheses using Vector Autoregression (VAR). The results obtained show that based on the results of the Impulse Response Function, the shock that occurs in the variables of liquidity CR, LR, FDR and CAR will have a higher impact on ROE financial performance than ROA and the impact will take around 45 months. Then based on the results of Variance Decomposition it can be seen that the CR and LR variables have the largest contribution to ROA with a contribution of 4.71%, while the CAR and LR variables are the variables that have the largest contribution to ROE with a contribution of 20.21%. These results indicate that the liquidity factors that have a major influence on the financial performance of Islamic banks in Indonesia are CAR, CR and LR, so as to maintain the financial performance of Islamic banks in Indonesia, it is necessary to control the CAR, CR and LR liquidity variables in good condition.